Online photovoice to engage indigenous Cook Islands youth in the exploration of social and ecological wellbeing amidst a global disruption - Waegh, Roxane de; Teaurere, Rerekura; Orams, Mark; Lück, Michael (Frontiers in Sustainable Tourism, 2023)
Photovoice is a participatory action research method that aims to include the voices of groups by enabling people to record and reflect on their knowledge of issues they consider important. Drawing from critical pedagogy, feminist theory, and community-based approaches to document research, photovoice involves participants as collaborators by using photographs that participants take themselves. Engaging the participants in conversations regarding their photographs facilitates agency in the research process and provides valuable insights into the views, experiences, and knowledge of participants. Originating in the public sector as a method for assessing health needs, the use of photovoice has since gained popularity as a tool for examining perceptions regarding changes in the social and natural environment, and for exploring human-environment interactions. This paper reviews the use of photovoice as a research method to engage indigenous youth in the small island community of Rarotonga, Cook Islands for the exploration of ecological and social wellbeing during disaster times. Amidst the global disruption ensued by the COVID-19 pandemic, indigenous youth participants explored the responses and adaptations of their community to changes in the social and ecological environment of their island home. Given the associated lockdown measures and travel restrictions, photovoice interviews were conducted via Zoom, an online videoconferencing platform. By integrating the photovoice method with advanced online communication systems, the research team based in Auckland, New Zealand was able to collect data remotely while facilitating meaningful engagement with indigenous youth participants across geographic and cultural borders. The use of online photovoice via Zoom was shown to be an empowering and inclusive method for the engagement of indigenous youth and the promotion of collaborative, cross-cultural research partnerships for the exploration of social and ecological wellbeing during a global disruption.